استخدام الزيوليت الطبيعي في أعمدة الوسط الثابت لإزالة المعادن الثقيلة من مياه الصرف الصناعي لمصفاة بانياس - سلمان هناء; شاهين هيثم; عباس غياث; خلوف نسرين (Latakia University Journal -Engineering Sciences Series, 2018)
تم استخدام أعمدة امتزاز بوسط ثابت من الزيوليت الطبيعي لدراسة حركية إزالة المعادن الثقيلة من محاليل أحادية المكون للفاناديوم والنيكل والزنك والرصاص. تتضمن بارامترات النظام المدروسة معدل تدفق المحلول وارتفاع الوسط. تم أيضاً دراسة تأثير الشوارد المنافسة ذلك لتقرير كفاءة الزيوليت الطبيعي في معالجة المياه الصناعية تحت ظروف مستمرة باستخدام أعمدة الوسط الثابت. كما تم تجديد الزيوليت الطبيعي المحمل بالمعدن باستخدام ملح كلور الصوديوم. أظهرت النتائج أن معدلات التدفق الأبطأ أعطت كفاءات إزالة أفضل بالمقارنة مع المعدلات الأسرع، ارتفاعات الوسط الأطول أدت أيضاً لكفاءات امتزاز أكبر. تم استخدام نموذج مدة خدمة عمق الوسط (BDST) بنجاح لمحاكاة النتائج التجريبية عند اختراق مقداره 30%. للحصول على البارامترات الضرورية التي نحتاجها لتصميم عمود الوسط الثابت. تراوحت قيم R2 بين0.91 و 0.95. تم تعريض الزيوليت الطبيعي لثلاث دورات من الامتزاز والاستخلاص، بينت النتائج أن كفاءات الاستخلاص لإزالة المعدن الثقيل كانت عالية مما يدل أنه يمكن إعادة إنتاج الزيوليت وإعادة استخدامه لإزالة المعادن الثقيلة من المحلول. Fixed bed adsorption columns packed with natural zeolite were used to study the kinetics of heavy metals removal from the single component solutions of Vanadium, Nikle, Zinc, and Lead. The system parameters studied include solution flow rate and bed height. The effect of competing cations was also studied to establish the effectiveness of natural zeolite in treating Industrial wastewater under continuous conditions using fixed bed columns. The metal loaded natural zeolite was regenerated using NaCl . The results from column studies showed that the Slower flow rates gave better removal efficiencies compared to faster ones, Longer bed heights also resulted in greater adsorption efficiencies. The bed depth service time (BDST) model was successfully used to simulate experimental results at 30 % breakthrough. This model provides the necessary parameters needed for fixed bed column design, the factor R2 ranged between 0.91 – 0.95. Natural zeolite was exposed to 3 cycles of adsorption and desorption. The efficiency of the column in removing heavy metals was high, The results indicate that natural zeolite can be regenerated and re-used in removing heavy metals from solution.